2021
DOI: 10.3389/fcvm.2021.658900
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Mechanisms Involved in the Cardiovascular Toxicity of Anticancer Drugs

Abstract: The cardiovascular toxicity of anticancer drugs promotes the development of cardiovascular diseases. Therefore, cardiovascular toxicity is an important safety issue that must be considered when developing medications and therapeutic applications to treat cancer. Among anticancer drugs, members of the anthracycline family, such as doxorubicin, daunorubicin and mitoxantrone, are known to cause cardiotoxicity and even heart failure. Using human-induced pluripotent stem cell-derived cardiomyocytes in combination w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Epigenetic mechanisms, which are crucial in transcriptional control of gene expression and implicated in adverse cardio-oncology outcomes, are largely understudied in the context of chronic PSES among cardio-oncology patients. 108 At present, most evidence is available on the epigenetic effects of doxorubicin in relation to cardiovascular outcomes. 108 , 109 Recently, a study suggested epigenetic memory after anthracycline therapy may lead to CVD.…”
Section: Sdoh and Biological Pathways In Cardio-oncologymentioning
confidence: 99%
See 1 more Smart Citation
“…Epigenetic mechanisms, which are crucial in transcriptional control of gene expression and implicated in adverse cardio-oncology outcomes, are largely understudied in the context of chronic PSES among cardio-oncology patients. 108 At present, most evidence is available on the epigenetic effects of doxorubicin in relation to cardiovascular outcomes. 108 , 109 Recently, a study suggested epigenetic memory after anthracycline therapy may lead to CVD.…”
Section: Sdoh and Biological Pathways In Cardio-oncologymentioning
confidence: 99%
“… 108 At present, most evidence is available on the epigenetic effects of doxorubicin in relation to cardiovascular outcomes. 108 , 109 Recently, a study suggested epigenetic memory after anthracycline therapy may lead to CVD. 110 Therefore, it is important to establish overlapping epigenetic pathways related to the effects of cancer therapy, experiences caused by adverse SDOH, and CVD outcomes to identify specific predictors and therapeutic targets for populations at highest risk for cardiotoxicity after cancer treatment.…”
Section: Sdoh and Biological Pathways In Cardio-oncologymentioning
confidence: 99%
“…Anthracyclines also activate pro-inflammatory pathways involving nuclear factor-kB (NF-kB) and tumor necrosis factor alpha (TNF-α) and upregulate the transcription of NLRP3, interleukin (IL)-1β and IL-6, key inflammatory mediators of heart failure pathogenesis (6). Cardiomyocyte death leads to further activation of inflammatory cascades and ROS production, leading to functional and structural changes in the myocardium that is marked by fibrosis and electrical alterations (7,8).…”
Section: Introductionmentioning
confidence: 99%